2016
DOI: 10.1016/j.powtec.2016.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of moist food powders as affected by moisture content

Abstract: Dynamic testing to determine rheological characteristics of moist food powders (semolina, coarse wheat flour, potato starch) was carried out using a powder rheometer of a new construction. The unique feature of the rheometer is that scale of shearing was confined to the thickness of shearing band of powder bed only. It was found that flow pattern of moistened samples was noticeably and diversely affected by both moisture content (varying in the range of 0-15% w/w) and shear rate. The observed changes showed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
1
19
0
2
Order By: Relevance
“…In this work an annular shear cell-type powder rheometer was used [24] and a simplified draft of this apparatus is given in Fig. 6.…”
Section: Rheology In Dynamic Conditionsmentioning
confidence: 99%
“…In this work an annular shear cell-type powder rheometer was used [24] and a simplified draft of this apparatus is given in Fig. 6.…”
Section: Rheology In Dynamic Conditionsmentioning
confidence: 99%
“…Opaliński et al [19] also explored the fact that the high level of moisture content resulted in increasing mechanical strength of the powder bed and poor powder flowability, particularly in a bad pattern of flow out of silos. Recently, Opaliński et al [65] observed that the moisture in food powders can act as a plasticizing agent for hygroscopic food powders such as semolina and coarse wheat powder, but it can also act as a lubricating factor for non-hygroscopic particles when flowing. In addition, the work of Juarez-Enriquez et al [62] found that hygroscopic food powders, especially pectin powder, modified its flowability from free-flow to cohesive powder as the water content of the powders increased due to the increase particles interactions by formation of liquid-bridges.…”
Section: Effect Of Moisture Content On the Flow Properties Of Powdermentioning
confidence: 99%
“…To characterize the flow properties of the powders, the shear cell technique is widely used [6] in designing storage bins and hoppers that are widely used in all kind of industrial processes, such as detergent, cement, food etc. [7][8][9]. However, it seems that there is a is too cohesive then segregation is no longer a problem, but poor flow and unwanted adhesion problems may occur instead.…”
Section: Accepted Manuscriptmentioning
confidence: 99%